Analisis Kerusakan pada Rotor Turbin Uap Kapasitas 3191 KW - Apriardi Ihlas (Balai Besar Bahan dan Barang Teknik, 2016)
The failure by corrosion of a 3191 KW steam turbine rotor was investigated. The corrosion has occurred on a steam turbine which results in lowering power capacity. A series of examinations were conducted including: visual examination, chemical composition, macro and micro examination, and Scanning Electron Microscopy/Energy Dispersive X-ray spectroscopy(SEM-EDS). Visual examination showed the location of corrosion tend to be more severe on the outer side. It has been found breakages in the form of a round shape holes. On the EDS examination, it was discovered that the element of silicon as a compiler of silica compounds, especially SiO2. A hard compound in the form of fine particles was suspected as the cause of damage through collision impact, which would be the initiation of further corrosion as pitting. Thus, the type of damage of this steam turbine's rotor, was the corrosion which caused by silica deposits carried away by the steam.Korosi pada turbin uap yang menyebabkan penurunan kapasitas daya. Telah dievaluasi untuk mengetahui penyebab kerusakan agar kejadian serupa tidak berulang kembali. Untuk itu, dilakukan serangkaian pemeriksaan yang meliputi: pemeriksaan visual, komposisi kimia bahan, pemeriksaan makro dan mikro, dan juga Scanning Electron Microscopy/Energy Dispersive X-ray spectroscopy (SEM-EDS). Pemeriksaan visual menunjukkan lokasi korosi cenderung semakin parah pada radius terluar dekat sudu. Bentuk kerusakan berupa lubang-lubang yang berbentuk bulat.. Pemeriksaan EDS ditemukan unsur silikon sebagai penyusun senyawa silika, khususnya SiO2. Senyawa keras yang berbentuk partikel halus ini diduga sebagai penyebab kerusakan melalui benturan yang akan menjadi inisiasi korosi lanjutan sebagai korosi lubang. Jadi, tipe kerusakan pada rotor turbin uap ini adalah korosi yang diakibatkan oleh deposit silika yang terbawa oleh uap boiler.